2016
DOI: 10.18632/aging.101084
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal hyperbaric normoxia treatment improves healthspan and regulates chitin metabolic genes in Drosophila melanogaster

Abstract: Aging is a universal, irreversible process accompanied by physiological declines that culminate in death. Rapid progress in gerontology research has revealed that aging can be slowed through mild stress-induced hormesis. We previously reported that hyperbaric normoxia (HN, 2 atm absolute pressure with 10% O2) induces a cytoprotective response in vitro by regulating fibronectin. In the present study, we investigated the hormetic effects of prenatal HN exposure on Drosophila healthspan related to molecular defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In our model, increased intrauterine ROS exposure appears to condition metabolic networks towards an improved response to an increasing oxidative and nutritional burden associated with the Western diet in adulthood. While we are not aware of comparable studies in a mammalian system, work in Drosophila indicated that increased oxidative stress due to hyperbaric pressure in early development resulted in increased resistance to oxidative stress in adult flies and an extended lifespan [24]. Hyperbaric oxygen chambers are in use as treatment for severe IUGR due to placental insufficiency [25].…”
Section: Discussionmentioning
confidence: 99%
“…In our model, increased intrauterine ROS exposure appears to condition metabolic networks towards an improved response to an increasing oxidative and nutritional burden associated with the Western diet in adulthood. While we are not aware of comparable studies in a mammalian system, work in Drosophila indicated that increased oxidative stress due to hyperbaric pressure in early development resulted in increased resistance to oxidative stress in adult flies and an extended lifespan [24]. Hyperbaric oxygen chambers are in use as treatment for severe IUGR due to placental insufficiency [25].…”
Section: Discussionmentioning
confidence: 99%
“…Genes from this category were shown to be highly up-regulated in flies exposed to mild stress by increased atmospheric pressure (hyperbaric normoxia) (Yu et al, 2016). This stress has been suggested to induce cytoprotective responses, aimed to protect cells or organisms against the detrimental effects of stressors, such as senescence (Oh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%